Correlation between C16orf74 expression and drug sensitivity. - Xiang-Rong Yao (21261870) (2025)
Scatter plots (a) and boxplots (b) showing the negative correlation between C16orf74 expression and sensitivity to various drugs. Statistical significance: *p < 0.05, **p < 0.01, ***p < 0.001.